PELAKSANAAN SUPERVISI AKADEMIK KEPALA SEKOLAH DI SEKOLAH LUAR BIASA - Evanofrita, Evanofrita; Rifma, Rifma; Nellitawati, Nellitawati (Graduate Program Magister Manajemen Pendidikan, 2020)
The target of educational supervision can determine the success of an educational institution, among others, students, teachers, curriculum, infrastructure, management, environment and the general situation of the school. The implementation of academic supervision by principals in several schools has not been successful in improving teacher performance. However, at SLB YPPLB Padang, academic supervision has been carried out by the school principal and is able to improve teacher performance. This was caused by several factors including: high school principal professionalism, adequate academic competency of school principals, teachers who were on average ready to be supervised especially teachers in low grades (Class I - IV), principals were able to create good relationship patterns with all components of the school, the principal is able to overcome obstacles in the implementation of academic supervision, and adequate and adequate school infrastructure for teaching and learning activities (KBM). SLB YPPLB Padang has arranged academic supervision program planning, carried out, and followed up on the results of supervision in accordance with what should be.